Genetic evidence for assortative mating on alcohol consumption in the UK Biobank - Laurence J. Howe; Daniel J. Lawson; Neil M. Davies; Beate St. Pourcain; Sarah J. Lewis; George Davey Smith; Gibran Hemani (Nature Communications, 2019)
From observational studies, alcohol consumption behaviours are known to be correlated in spouses. Here, Howe et al. use partners’ genotypic information in a Mendelian randomization framework and show that a SNP in the ADH1B gene associates with partner’s alcohol consumption, suggesting that alcohol consumption affects mate choice.